ANALISIS PENGGUNAAN MAJAS YANG TERKANDUNG DALAMA CERPEN BERJUDUL “PATAH DAN RASA YANG BERDARAH” KARYA NIAM KHUROTUL ASMA - Feni Amanda Putri; Khairu Zahra Nasution; Sarah Humala Lubis; Fitriani Lubis (FKIP, Universitas Palangka Raya, 2023)
This study aims to determine the use of figure of speech contained in a short story entitled “Broken and Bleeding Taste” Karrya Nian Khurotul Asma. Research examining the use of figure of speech has been carried out by several researchers. This research method is a qualitative descriptive method with the results in the form of narrative data according to the approach used. Based on the data collected, it contains several language styles (majas), namely of which there are 5 personification majas, there are 4 metaphors, there is only 1 allegory, there is 1 smile and there is 1 satire.